Encyclopedia of children and childhood in history and society - Fass, Paula S.; Gale Group (New York Macmillan Reference USA, 2004)
"Readers are assured the latest interdisciplinary scholarship from an emerging field of study that examines the social history of children and childhood. Some 445 expertly written articles bring new insight and understanding about the lived experiences of children and the many complex cultural meanings ascribed to childhood. Emphasizing social history yet treating a broad range of related topics, the set also contains a thematic outline of contents, comprehensive index, and appendix that lists important primary sources."--"Reference that rocks," American Libraries, May 2005.
This 3-vol. set presents the social and cultural history of childhood from antiquity to the present. Children and Childhood examines this history through articles on education, parenting, child labor, economics, images of childhood, children's literature, play, toys and games, health, physiology, law, the criminal justice system and social welfare.
v. 1. A - E -- v. 2. F - R -- v. 3. S - Z; Primary sources; Index.
Electronic reproduction.
Keywords: Children -- Encyclopedias; Electronic books